Numerical simulation of convective heat transfer in a turbulant non-Newtonian nanofluid flow through a horizontal circular tube - mohammad sharifi Asl; davood toghraie; AhmadReza Azimian (مجله مدل سازی در مهندسی, 2018)
In this paper, a numerical study on the convective heat transfer characteristics in a non-Newtonian nanofluid flow in the horizontal tube with constant heat flux is carried out using computational fluid dynamics (CFD). The primary objective is to evaluate the effect of using nanoparticles on convective heat transfer coefficient. For this purpose, non-Newtonian nanofluid containing Al2O3 and 0.5 wt.%. Aqueous solution of carboxymethyl cellulose (CMC) as a liquid single phase with two particle concentrations of 0.5 and 1.5 vol. % were used. Effect of particle concentrations on convective heat transfer coefficient was investigated in different Reynolds numbers (4500